HRM practices and organizations' internal context role in performance - Pires, M. L.; Nunes, F. G. (European Journal of Applied Business and Management, 2015)
Purpose - The main purpose of the present study is to test the association between Human Resource Management practices (HRMP) perceptions, internal context, and organizational performance. Design/methodology/approach - The data was collected based on a sample of 525 individuals from 22 stores, with performance indicators collected at the store level. Findings - The results showed (a) a positive relationship between perceived organizational integrity and organizational performance, as well as a negative relationship with staff turnover; (b) and a negative relationship between employment conditions and staff turnover. Research limitations/implications - The small sample size and the fact that the study was conducted in stores of the same organization doesn’t allow generalization of findings; results are based on data from cross-sectional design, longitudinal data would be needed to infer causal relationships. Practical implications - Managers should take in consideration that organizational integrity, as perceived by employees, can enhance organizational performance and reduce turnover, better employment conditions will also have this effect in turnover. Originality/value - These findings allow us to discuss the role of HRMP and of organizations internal context and characteristics on performance.